Dynamically Tunable Dual-Frequency Terahertz Absorber Based on Graphene Rings - Wei Su; Xinyue Chen; Zhen Geng (IEEE Photonics Journal, 2019)
A dual-frequency absorber with periodic double-layer graphene ring arrays separated by dielectric spacer is proposed. Coupled-mode theory and finite difference time domain method are used to analyze the perfect absorption and the absorption mechanism. Moreover, the influences of structural parameters and chemical potential of graphene on the peak positions have been investigated. Benefiting from chemical potential can be controlled by external bias voltage, thus the proposed structure can be used as a dynamically tunable absorber. Such simple absorber has potential applications in optical storage devices and frequency-selective detectors for terahertz regime.